Sex as Spoken Words in Contemporary British Drama - Alexander Millington (MediAzioni)
This paper focuses on the descriptive acts of sex and intimacy on the contemporary British stage as written texts and spoken words. The paper will specifically be exploring the use of language in Katherine Chandler’s Lose Yourself (2019) and Anna Jordan’s Freak (2014). Both of these play texts use language to describe in varying detail the intimate acts that the characters are recounting, some violent, some messy, some simply underwhelming, but it is solely the description of the acts that the audience are party too. The article refers to extracts from the published texts as well as critic responses of the performances, and apply theories from George Rodosthenous’s collection of essays, Theatre As Voyeurism (2015), exploring the acceptance of audio and visual voyeurism on stage, and Lisa Fitzpatrick’s Rape on The Contemporary State (2018) with regard to the issues that arise when performing violent sexual acts on stage. By using these critical texts and relating the author’s theories to my chosen performance texts, I argue that by using the description of the sexual acts, rather than overtly performing them, the intimate, aural connection that occurs between the performer and the spectator can be greater than the visual. As society seems to continuously change its mind about what is and is not acceptable to portray on stage, is the aural description of sexual and intimate acts bridging the gap of censorship, putting the ownership on the spectator’s imagination, rather than the performers’ interpretation?